Seedling dynamics and subsequent production of annual Medicago spp. as affected by pasture utilization, seedbed preparation and soil type - Kotze, Theunis Nicolaas (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph.D. Agric.) -- University of Stellenbosch, 1999.